2018
DOI: 10.1093/mnras/sty396
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the linear bias models in the light of the Dark Energy Survey

Abstract: The evolution of the linear and scale independent bias, based on the most popular dark matter bias models within the ΛCDM cosmology, is confronted to that of the Dark Energy Survey (DES) Luminous Red Galaxies (LRGs). Applying a χ 2 minimization procedure between models and data we find that all the considered linear bias models reproduce well the LRG bias data. The differences among the bias models are absorbed in the predicted mass of the darkmatter halo in which LRGs live and which ranges between ∼ 6 × 10 12… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…The second result is that the differences of the bias models are absorbed in the fitted value of the DM halo mass in which LRGs live, and which ranges from ∼ 6.2 × 10 12 h −1 M ⊙ − 1.2 × 10 13 h −1 M ⊙ , for the different bias models and in the case of DESY1COSMO bias. As it can also be seen from Table II, our derived mass of the host DM halo mass is consistent with that of Papageorgiou et al [61], while Sawangwit et al [62] and Pouri et al [63] found M h ≃ (1.9 − 2) × 10 13 h −1 M ⊙ .…”
Section: Constant Growth Indexsupporting
confidence: 91%
“…The second result is that the differences of the bias models are absorbed in the fitted value of the DM halo mass in which LRGs live, and which ranges from ∼ 6.2 × 10 12 h −1 M ⊙ − 1.2 × 10 13 h −1 M ⊙ , for the different bias models and in the case of DESY1COSMO bias. As it can also be seen from Table II, our derived mass of the host DM halo mass is consistent with that of Papageorgiou et al [61], while Sawangwit et al [62] and Pouri et al [63] found M h ≃ (1.9 − 2) × 10 13 h −1 M ⊙ .…”
Section: Constant Growth Indexsupporting
confidence: 91%
“…We have fitted two different bias evolution models to the data, the Basilakos et al (2008) and the Tinker et al (2010) models, using a χ 2 minimization procedure and we derive the DM host halo mass (details and comparisons of the different bias models can be found in Papageorgiou et al 2012Papageorgiou et al , 2018. We find log 10 M h /[h −1 M ] = 13.04 ± 0.06 and 12.98 ± 0.07 for the two models, respectively.…”
Section: Resultsmentioning
confidence: 99%